1992
DOI: 10.1128/jvi.66.1.106-114.1992
|View full text |Cite
|
Sign up to set email alerts
|

The position of heterologous epitopes inserted in hepatitis B virus core particles determines their immunogenicity

Abstract: The nucleocapsid (HBcAg) of the hepatitis B virus (HBV) has been suggested as a carrier moiety for vaccine purposes. We investigated the influence of the position of the inserted epitope within hybrid HBcAg particles on antigenicity and immunogenicity. For this purpose, genes coding for neutralizing epitopes of the pre-S region of the HBV envelope proteins were inserted at the amino terminus, the amino terminus through a precore linker sequence, the truncated carboxy terminus, or an internal site of HBcAg by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(77 citation statements)
references
References 38 publications
3
73
1
Order By: Relevance
“…Taken together, these data clearly show that the insertion of heterologous epitopes in core-like particles modified and determined their immunogenicity. Such an observation was also made and a similar conclusion reached when neutralizing epitopes of the pre-S region of the hepatitis B virus envelope were inserted at different places of the viral core protein [Schödel et al, 1992].…”
Section: Discussionsupporting
confidence: 60%
“…Taken together, these data clearly show that the insertion of heterologous epitopes in core-like particles modified and determined their immunogenicity. Such an observation was also made and a similar conclusion reached when neutralizing epitopes of the pre-S region of the hepatitis B virus envelope were inserted at different places of the viral core protein [Schödel et al, 1992].…”
Section: Discussionsupporting
confidence: 60%
“…Another consequence of these deletions would be loss of the HBe2 determinant because the remaining amino acids would constitute <90% of the full length protein. Schodel et al [1992] have demonstrated that insertion of a pre-S(l) epitope sequence into the core gene, which resulted in expression of the epitope between amino acids 75 and 83 of the HBcAg, dramatically reduced both the antigenicity and immunogenicity of the capsid protein. Such reduction was not observed if the foreign epitope was inserted at the 5' or 3' ends of the core gene.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that practically all core protein in hepatocytes of chronic HBV carriers is assembled in core particles is also relevant to the host immune responses. The particulate core protein is more immunogenic than the denatured forms [Schödel et al, 1992]. In athymic mice only the particulate form of HBcAg was able to induce a T cell-independent antibody response [Milich et al, 1986].…”
Section: Discussionmentioning
confidence: 99%